A case study of organisational change in an employee wellness company and its effects on job satisfaction and organisational climate - Kassiem, Wahib (Rhodes University, Faculty of Commerce, Rhodes Business School, 2015)
The modern era has brought the phenomenon of organisational change closer to the average person. With the recent financial crisis placing more strain on businesses, organisations are always under pressure to review their business models in order to deliver a sustainable operational model and as result, hopefully a sustainable competitive advantage. In order to remain competitive, the leadership team has to constantly seek ways of differentiating their organisations from others with similar product offerings. When these changes are initiated, there is no doubt that the leadership gave extensive thought prior to execution. However, their motives are not always clear to their most important constitution, their employees. Often when these changes are implemented, employees believe that they've been left out of the decision making process. Furthermore, post change review with employees are also not given enough thought and are often not done. This research used qualitative research methods to establish how employees experience job satisfaction and organisational climate subsequent to changes that transpired within their work environment. Semi-structured interviews and document analysis were used to collect data. The interviews were constructed by expanding upon well-documented quantitative dimensions of these behavioural variables. Questions were developed focusing on these dimensions in line with the changes experienced. The sample consisted of nine employees at an employee wellness organisation in Roodepoort, Gauteng. There is evidence to show that in this short period of two years (May 2012 to June 2014), by implementing various changes, the new leadership has improved the financial viability of the organisation. However, insights from the interviews point to a number of areas where the leadership and management structures have to exert more effort. Communication processes have to be reviewed, especially to lower levels. As there exists limited opportunities for promotion, investigations into expanding existing roles, again at the lower levels may assist in raising job satisfaction levels. Employees felt that support structures are severely lacking when significant changes affecting them are implemented. A climate for innovation and risk taking has to be considered which, if instituted, could aid the organisation in setting the pace for the organisational wellness industry. The structure adopted for this research consists of three sections. Section one follows the evaluation report format, with the literature review and research methodology sections following thereafter. By making use of established literature as a basis, the findings and recommendations are therefore not exclusively applicable to this organisation. Hence other organisations intending similar change initiatives could benefit from this research.
Keywords: Organizational change -- South Africa -- Case studies